Obstructive pancreatolithiasis in a cat with triaditis and concurrent hypercalcaemia. Issue 1 (March 2021) - Allan, Frederik; Peschard, Anne-Lorraine; Schiavo, Luca; Bayton, Will; Corbetta, Davide; McCallum, Katie E
Case summary: A 7-year-old neutered female domestic longhair cat was presented for further investigation of suspected hepatobiliary disease. Increases in serum 1, 2-o-dilauryl-rac-glycero-3-glutaric acid-(6'-methylresorufin) ester lipase and hepatobiliary enzymes, with concurrent hypoalbuminaemia, were documented on blood biochemistry. Abdominal ultrasonography findings were consistent with acute pancreatitis with multiple pancreatoliths visualised within the pancreatic duct. Treatment for suspected triaditis was initiated with a hydrolysed protein diet, amoxicillin–clavulanate, hepatoprotectants and buprenorphine. Fifty-three days later, the patient presented with hypercalcaemia and obstructive pancreatolithiasis, and was euthanased. Post-mortem examination revealed severe chronic active pancreatitis with moderate chronic lymphocytic, plasmacytic cholangiohepatitis and mild chronic lymphocytic–plasmacytic duodenal enteritis (triaditis). Multiple calcium carbonate pancreatoliths present within the pancreatic ducts had resulted in pancreatic duct obstruction. Relevance and novel information: Pancreatolithiasis is a very rare condition in cats, with only five reports to date. In human medicine, pancreatolithiasis is often a sequala to chronic pancreatitis, seen in up to 50–90% of patients. However, in cats the aetiology of pancreatolithiasis, and indeed chronic pancreatitis, is poorly understood. This report describes a case of obstructive pancreatolithiasis in a cat with histopathological confirmation of triaditis and is the first report of hypercalcaemia in a cat with obstructive pancreatolithiasis. This further adds to the evidence base that pancreatolithiasis may have a similar pathogenesis to humans and can develop secondarily to chronic pancreatitis in cats.